GENE-40. CHARACTERIZING EPIGENETIC INTRATUMORAL HETEROGENEITY IN GLIOMA USING SINGLE-CELL BISULFITE SEQUENCING. (11th November 2019) - Johnson, Kevin C; Anderson, Kevin; Courtois, Elise; Barthel, Floris; Samuels, Michael; Robson, Paul; Bulsara, Ketan; Das, Sunit; Verhaak, Roel
Abstract: Genetic and epigenetic alterations contribute to the observed intratumoral heterogeneity in adult glioma. Current glioma classification, based on genotype (e.g., IDH1 mutations) and DNA methylation profiles (e.g., glioma CpG Island Methylator Phenotype), can provide clinically relevant tumor subgroups. However, traditional bulk sampling fails to adequately capture the full complement of epigenomic heterogeneity, and may mask deadly features present in less abundant glioma cells. To more precisely characterize the glioma epigenome, we separately profiled single-cell DNA methylation (Reduced Representation Bisulfite Sequencing, RRBS), single-cell RNA expression (10X genomics), and bulk whole genome sequencing in nine gliomas. The genomic regions profiled by scRRBS were primarily gene promoters, but adequate coverage was also reached for glioma-specific enhancer elements and binding sites of chromatin remodelers. Unsupervised clustering of single-cell DNA methylation data revealed intratumoral variability in epigenetic classification and these cell types were distinguished by regulatory element DNA methylation. We further integrated single-cell epigenetic, single-cell transcriptomic, and genomic features to better understand gene regulation and reconstruct each tumor's lineage history. Together, our study aims to generate a glioma cellular hierarchy shaped by the epigenetic programs that drive tumor growth.